Novel hexadentate and pentadentate chelators for (64)Cu-based targeted PET imaging - Sin, Inseok (2014)
A series of new hexadentate and pentadentate chelators were designed and synthesized as chelators of (64)Cu. The new pentadentate and hexadentate chelators contain different types of donor groups and are expected to form neutral complexes with Cu(II). The new chelators were evaluated for complex kinetics and stability with (64)Cu. The new chelators instantly bound to (64)Cu with high labeling efficiency and maximum specific activity. All (64)Cu-radiolabeled complexes in human serum remained intact for 2 days. The (64)Cu-radiolabeled complexes were further challenged by EDTA in a 100-fold molar excess. Among the (64)Cu-radiolabeled complexes evaluated, (64)Cu-complex of the new chelator E was well tolerated with a minimal transfer of (64)Cu to EDTA. (64)Cu-radiolabeled complex of the new chelator E was further evaluated for biodistribution studies using mice and displayed rapid blood clearance and low organ uptake. (64)Cu-chelator E produced a favorable in vitro and in vivo complex stability profiles comparable to (64)Cu complex of the known hexadentate NOTA chelator. The in vitro and in vivo data highlight strong potential of the new chelator E for targeted PET imaging application.